Surface Treatment by Different Parameters of Erbium:Yttrium–Aluminum–Garnet (Er:YAG) Laser: Scanning Electron Microscope (SEM) Evaluation - Chiniforush, Nasim; Nokhbatolfoghahaei, Hanieh; Monzavi, Abbas; pordel, Edris; Ashnagar, Sajjad (Journal of Lasers in Medical Sciences, 2016)
Introduction: This study aimed to assess the Scanning Electron Microscope (SEM) analysis of tooth surface irradiated by erbium:yttrium–aluminum–garnet (Er:YAG) laser with various parameters. Methods: Number of 25 extracted human third molars free of caries were used in this study. The teeth were put into 5 groups for laser irradiation as follows: group 1 (power: 0.5 W, Energy: 50 mJ); group 2 (power: 1 W, Energy: 100 mJ); group 3 (power: 1.5 W, Energy: 150 mJ); group 4 (power: 2 W, Energy: 200 mJ); group 5 (power: 2.5 W, Energy: 250 mJ). All samples were prepared by repetition rate of 10 Hz and duration of 230 μs, using a non-contact handpiece at a distance of 4 mm. Then, the samples were prepared for SEM examination. Results: SEM evaluation of every 25 samples, treated by Er:YAG, showed that all groups had exposed dentinal tubules without any melted area or cracks. Conclusion: In this study we used SEM to investigate ablated dentine with different parameters of Er:YAG laser energy. Our findings support these conclusions. All powers of laser below 3 W are proper for ablation, and make no cracks.